Mammalian mitochondrial translation infidelity leads to oxidative stress–induced cell cycle arrest and cardiomyopathy - Wen-Qiang Zheng; Jianhui Zhang; Zi-Han Li; Xiuxiu Liu; Yong Zhang; Shuo Huang; Jinsong Li; Bin Zhou; Gilbert Eriani; En‐Duo Wang; Xiao-Long Zhou (2023)
Proofreading (editing) of mischarged tRNAs by cytoplasmic aminoacyl-tRNA synthetases (aaRSs), whose impairment causes neurodegeneration and cardiac diseases, is of high significance for protein homeostasis. However, whether mitochondrial translation needs fidelity and the significance of editing by mitochondrial aaRSs have been unclear. Here, we show that mammalian cells critically depended on the editing of mitochondrial threonyl-tRNA synthetase (mtThrRS, encoded by Tars2 ), disruption of which accumulated Ser-tRNA Thr and generated a large abundance of Thr-to-Ser misincorporated peptides in vivo. Such infidelity impaired mitochondrial translation and oxidative phosphorylation, causing oxidative stress and cell cycle arrest in the G0/G1 phase. Notably, reactive oxygen species (ROS) scavenging by N-acetylcysteine attenuated this abnormal cell proliferation. A mouse model of heart-specific defective mtThrRS editing was established. Increased ROS levels, blocked cardiomyocyte proliferation, contractile dysfunction, dilated cardiomyopathy, and cardiac fibrosis were observed. Our results elucidate that mitochondria critically require a high level of translational accuracy at Thr codons and highlight the cellular dysfunctions and imbalance in tissue homeostasis caused by mitochondrial mistranslation.